ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMANFAATAN ‘NRC ORACLE’ DI PT. NUSA RAYA CIPTA, TBK KANTOR CABANG DENPASAR - Suryaningsih, Ika Setiawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The objective of this research is to explain and predict factors that affect the intention of use NRC Oracle through Unified Theory of Acceptance and Use of Technology. This study was carried out in PT. Nusa Raya Cipta, Tbk branch of Denpasar. The respondents of this study are 82 employees who use NRCO in their operation. The data were analyzed in SPSS 20. The results of the analysis indicate that effort expectancy variable and social factor variable give positive influence to the intention to use NRC Oracle. However, performance expectancy variable and facilitating condition variable give negative influence to the intention to use NRC Oracle.Keywords: Performance expectancy, effort expectancy, social factor, facilitating conditions, behavioral intention of information system